Biomimetic [2Fe-2S] Clusters with Extensively Delocalized Mixed-Valence Iron Centers - Yao, Shenglai; Meier, Florian; Lindenmaier, Nils; Rudolph, Robert; Blom, Burgert; Adelhardt, Mario; Sutter, Jörg; Mebs, Stefan; Haumann, Michael; Meyer, Karsten; Kaupp, Martin; Driess, Matthias (Angewandte Chemie International Edition, 2015)
A complete series of biomimetic [2Fe-2S] clusters, [((LFe)-Fe-Dep)(2)(mu-S)(2)] (3, L(De)p = CH[CMeN(2,6-Et2C6H3)](2)), [((LFe)-Fe-Dep)(2)(mu-S)(2)K] (4), [(L(De)pFe)(2)(mu-S)(2)][Bu4N] (5, Bu=n-butyl), and [((LFe)-Fe-Dep)(2)(mu-S)(2)K-2] (6), could be synthesized and characterized. The all-ferric [2Fe-2S] cluster 3 is readily accessible through the reaction of [((LFe)-Fe-Dep)(2)(mu-H)(2)] (2) with elemental sulfur. The chemical reduction of 3 with one molar equivalent of elemental potassium affords the contact ion pair K+[2Fe-2S](-) (4) as a one-dimensional coordination polymer, which in turn reacts with [Bu4N] Cl to afford the separate ion pair [Bu4N](+)[2Fe-2S](-) (5). Further reduction of 4 with potassium furnishes the super-reduced all-ferrous [2Fe-2S] cluster 6. Remarkably, complexes 4 and 5 are [2Fe-2S] clusters with extensively delocalized Fe2+Fe3+ pairs as evidenced by Fe-57 Mossbauer, X-ray absorption and emission spectroscopy (XAS, XES) and in accordance with DFT calculations.
Keywords: iron; mixed-valence compounds; Rieske clusters; sulfur; beta-diketiminato ligands